2020
DOI: 10.11591/ijeecs.v19.i1.pp442-450
|View full text |Cite
|
Sign up to set email alerts
|

Towards electronic learning features in education 4.0 environment: literature study

Abstract: This paper presents electronic learning features in Education 4.0 environment. Malaysian government encourages Higher Education Institution (HEIs) to embed technologies in order to prepare future education (Education 4.0). Besides, developing skills among students is important to be more adaptable in changing the environment. Current HEIs using Learning Management System (LMS) has lack of interactive features and non-personalized learning. Therefore, this article set out to analyze the existing literature on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
0
20
0
3
Order By: Relevance
“…The blend learning model is one of the examples present to handle the potential harnessing digital technologies. Model is developed for students' online learning and self-directed learning awareness [25]. Sustainable education 4.0 is impossible without the involvement and accessibility of the Internet of Things (IoT) in industrial revolution 4.0, where machines are an integral part of social and economic development [26].…”
Section: Education 40mentioning
confidence: 99%
“…The blend learning model is one of the examples present to handle the potential harnessing digital technologies. Model is developed for students' online learning and self-directed learning awareness [25]. Sustainable education 4.0 is impossible without the involvement and accessibility of the Internet of Things (IoT) in industrial revolution 4.0, where machines are an integral part of social and economic development [26].…”
Section: Education 40mentioning
confidence: 99%
“…This means that individuals are asked to be advanced in finding solutions to emerging social problems and to utilize technology, economy and intellectual abilities in the context of sustainable welfare [1]- [5]. The emergence of industry 5.0 was caused by the failure of industry 4.0 which made individuals as an instant gratification where individuals became impatient figures, impulsive, and quick fulfilment of satisfaction [6]- [8]. This raises its problems in individual life, for it reduces the individual's fighting power to get things until Japan finally came up with its idea to develop the industry 5.0 era to balance technology and resolution for social problems and achieve sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronous e-learning have been increased due to proven demands in a number of eras such as education. Autthors in [7,8] concluded that e-learning embedded features in LMS will assist the tutor to generate a strategic learning features to suite the students' skills and style of learning, An interactive features of knowledge sharing, communication and information desimmination can be attained from utilizing e-learning.active learning can be achieved from differnet platforms like LMS, website, online database and social media platforms to enhance students' knowledge and discover different skills.…”
Section: Introductionmentioning
confidence: 99%